Surgical versus non-surgical treatment for vertebral compression fracture with osteopenia: a systematic review and meta-analysis. - Jia-Bao Guo; Yi Zhu; Bing-Lin Chen; Bin Xie; Wen-Yi Zhang; Yu-Jie Yang; Yu-Shan Yue; Xue-Qiang Wang (PLoS ONE)
Background Surgical and non-surgical interventions are the two categories for treatment of vertebral compression fractures (VCFs). However, there is clinical uncertainty over optimal management. This study aimed to examine the safety and effectiveness of surgical management for treatment of VCFs with osteopenia compared with non-surgical treatment. Methods We conducted a systematic search through electronic databases from inception to June 2014, with no limits on study data or language. Randomized controlled trials (RCTs) evaluating surgical versus non-surgical interventions for treatment of patients with VCFs due to osteopenia were considered. Primary outcomes were pain and adverse effects. A random-effects model was used to calculate the pooled mean difference (MD) or risk ratios with 95% confidence interval (CI). Results Sixteen reports (11 studies) met the inclusion criteria, and provided data for the meta-analysis with a total of 1,401 participants. Compared with conservative treatment, surgical treatment was more effective in reducing pain (short-term: MD -2.05, 95% CI -3.55 to -0.56, P=0.007; mid-term: MD -1.70, 95% CI -2.78 to -0.62, P=0.002; long-term: MD -1.24, 95% CI -2.20 to -0.29, P=0.01) and disability on the Roland-Morris Disability score (short-term: MD -4.97, 95% CI -8.71 to -1.23, P=0.009), as well as improving quality of life on the Short-Form 36 Physical Component Summary score (short-term: MD 5.53, 95% CI 1.45 to 9.61, P=0.008) and the Quality of Life Questionnaire of the European Foundation for Osteoporosis score (short-term: MD -5.01, 95% CI -8.11 to -1.91, P=0.002). Indirect comparisons between vertebroplasty and kyphoplasty found no evidence that the treatment effect differed across the two interventions for any outcomes assessed. Compared with the sham procedure, surgical treatment showed no evidence of improvement in pain relief and physical function. Based on these two comparisons, no significant difference between groups was noted in the pooled results for adverse events. Conclusion Compared to conservative treatment, surgical treatment was more effective in decreasing pain in the short,mid and long terms. However, no significant mid- and long-term differences in physical function and quality of life was observed. Little good evidence is available for surgical treatment compared with that for sham procedure. PV and BK are currently used to treat VCFs with osteopenia, with little difference in treatment effects. Evidence of better quality and from a larger sample size is required before a recommendation can be made. Systematic review registration http://www.crd.york.ac.uk/PROSPERO PROSPERO registration number: CRD42013005142.